Bilateral Choanal Atresia in 34 Year-old Patients - Tinoco, Paulo; Pereira, José Carlos Oliveira; Filho, Rodolfo Caldas Lourenço; Brito, Thiego Silveira Cajubá; Pereira, Betina Mameri; Carrara, Vânia Lúcia; Godoy, Sueliana Marta F. (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Choanal atresia (CA) can be defined as a failure to develop the communication between the nasal cavity and nasopharynx. May occur as a plate osteo-membranous, bony or membranous. Diagnosis depends on high clinical suspicion and laboratory tests, treatment is surgical.Objective: To report a case of an adult patient diagnosed with bilateral choanal atresia and underwent surgery.Case Report: MLSM, 34 years old female with a history of bilateral nasal obstruction, rhinorrhea hyaline since childhood. On nasal endoscopy and CT scan of the sinuses showed bilateral membranous atresia osteo. Patient underwent endoscopic transnasal route, with production of mucosal flap covering the wound, without stent placement. Tomography was performed which showed control choanae open and broad. The patient progressed well and has normal nasal breathing.Conclusion: AC bilateral, although rare, can occur in adult patients.
Keywords: choanal atresia; nasal obstruction; endoscopy; early diagnosis